Medicalized metamorphosis: biological rehabilitation of criminal offenders - Chandler, Jennifer A. (Critical criminology, 2021)
Convicted offenders who consent to medical treatment may secure a preferable sentence. They make these decisions within a hybrid medico-legal system that often views offenders as neurobiological subjects and deviant behavior as a medical problem that may be addressed, in part, through biological intervention. In this article, we use Foucault’s concepts of biopower and governmentality to explore how 15 men and 10 women convicted of criminal offenses view "coerced" consent to biological interventions in the criminal justice context. The participants largely accepted the key components of the medico-legal system of social control, including the medicalization of criminalized behavior, the utility of rehabilitation via medical treatment, and the internalization of the governmental ideals of self-control and responsibility. None challenged the use of biological treatments, although many rejected invasive and risky therapies, and most felt that biological approaches should be accompanied by psychological counseling. While governmental ideals were largely internalized, the participants expressed resistance in several ways, through statements of distrust of the system and resentment of pressure to consent to treatment.